Keeping young researchers out of harm’s way: conducting youth participatory action research with young people experiencing homelessness - Ratliff, G. Allen; Cosgrove, Darren; Yang, Jessica O.; Sarabia, Richard; Harvey, Taylor L.; Jeffcoat, Nathan; Lightfoot, Marguerita; Adams, Sherilyn; Lund, Ilsa; Auerswald, Colette L. (Frontiers in Public Health, 2024)
Introduction Youth Participatory Action Research (YPAR) is an approach to conducting research with youth populations in order to effectively engage youth in research that impacts their lives. Young people experiencing homelessness (YEH) are vulnerable to power and social environments in ways that call attention to their experiences in research. Methods The context for this paper was a qualitative YPAR project to incorporate youth voice into the operations of a larger research study that hired youth as researchers. Participant-researchers provided feedback and consultation with senior staff in order to improve their access to resources, safety, and stability. Results Themes that emerged from thematic analysis of reflections, discussions, and meetings showed the need for consistent access to food, the risk of environmental violence targeting youth researchers, the structural and experiential barriers to professional engagement, and the benefits that young researchers experienced as part of their work in the study. Discussion Recommendations and lessons learned are described, notably to ensure that youth are paid and provided food, to construct effective safety plans during fieldwork, and to provide a flexible, inclusive, trauma-responsive approach to supervision of project tasks.